Lower motor neuron dysfunction in ALS. Issue 7 (July 2016) - de Carvalho, Mamede; Swash, Michael
Highlights: Progressive lower motor neuron loss is a diagnostic marker of motor neuron disease–amyotrophic lateral sclerosis. Needle electromyography is a sensitive method to detect reinnervation, but quantifying lower motor neuron loss requires more sophisticated techniques. Several recent methods are promising in providing ancillary information when applied in addition to conventional electromyography. Abstract: In the motor system there is a complex interplay between cortical structures and spinal cord lower motor neurons (LMN). In this system both inhibitory and excitatory neurons have relevant roles. LMN loss is a marker of motor neuron disease/amyotrophic lateral sclerosis (MND/ALS). Conventional needle electromyography (EMG) does not allow LMN loss to be quantified. Measurement of compound muscle action potential (CMAP) amplitude or area, and the neurophysiological index, provide a surrogate estimate of the number of functional motor units. Increased motor neuronal excitability is a neurophysiological marker of ALS in the context of a suspected clinical and electrophysiological diagnosis. In the LMN system, fasciculation potentials (FPs) are the earliest changes observed in affected muscles, a feature of LMN hyperexcitability. Reinnervation is best investigated by needle EMG although other methods can be explored. Moreover needle EMG give information about the temporal profile of the reinnervation process, important ancillary data. Quantitative motor unit potential analysis is a valuable method of evaluating reinnervation. The importance of FPs has been recognized in the Awaji criteria for the electrodiagnosis of ALS, criteria that are a sensitive adjunct to the revised El Escorial criteria. Finally, functionality of LMN's, and perhaps excitability studies in motor nerves, aids understanding of the disease process, allowing measurement of potential treatment effects in clinical trials. Other investigational techniques, such as electrical impedance myography, muscle and nerve ultrasound, and spinal cord imaging methods may prove useful in future.